PERBEDAAN JUMLAH TRIGLISERIDA PADA REMAJA PEMAIN SEPAK BOLA DAN BUKAN SETELAH 30 MENIT - Gunma, San; Huldani, Huldani; Kaidah, Siti; Asnawati, Asnawati; Hendriyono, F X (Homeostasis, 2023)
Physical activity resulting from skeletal muscle contractions will result in energy expenditure from within the body which affects the decrease in triglyceride levels. This study aims to explain the difference in decreasing triglyceride levels before and after 30 minutes of running at moderate intensity in adolescent football players and non-ball players. The study was conducted using a quasi-experimental non-control group design on 15 trained adolescents and 15 untrained adolescents in Banjarmasin. The sampling technique was carried out by purposive sampling method. Triglyceride levels were measured before and after 30 minutes of moderate-intensity running followed by measurements of height and weight in both groups of adolescents. Data analysis used paired t-test (before and after) and unpaired t-test (trained and untrained) and Shapiro Wilk test. The results of the data analysis using Shapiro Wilk were not normally distributed, after which the data was transformed to Log 10. The results of the data analysis showed that there was no significant difference (p=0.786) between the triglyceride levels of youth football players and non-ball players. The results of this study concluded that there was no difference in triglyceride levels in trained and untrained adolescents after 30 minutes of moderate intensity running.